Single‐Ion Magnetic Behaviour in an Iron(III) Porphyrin Complex: A Dichotomy Between High Spin and 5/2–3/2 Spin Admixture. Issue 62 (30th September 2020) - Viciano‐Chumillas, Marta; Blondin, Geneviève; Clémancey, Martin; Krzystek, Jurek; Ozerov, Mykhaylo; Armentano, Donatella; Schnegg, Alexander; Lohmiller, Thomas; Telser, Joshua; Lloret, Francesc; Cano, Joan
Abstract: A mononuclear iron(III) porphyrin compound exhibiting unexpectedly slow magnetic relaxation, which is a characteristic of single‐ion magnet behaviour, is reported. This behaviour originates from the close proximity (≈550 cm −1 ) of the intermediate‐spin S= 3/2 excited states to the high‐spin S= 5/2 ground state. More quantitatively, although the ground state is mostly S= 5/2, a spin‐admixture model evidences a sizable contribution (≈15 %) of S= 3/2 to the ground state, which as a consequence experiences large and positive axial anisotropy ( D= +19.2 cm −1 ). Frequency‐domain EPR spectroscopy allowed the m S = |±1/2⟩→|±3/2⟩ transitions to be directly accessed, and thus the very large zero‐field splitting in this 3d 5 system to be unambiguously measured. Other experimental results including magnetisation, Mössbauer, and field‐domain EPR studies are consistent with this model, which is also supported by theoretical calculations. Abstract : Admix it up : The first mononuclear high‐spin d 5 ( S= 5/2) iron(III) compound that shows both in‐plane magnetic anisotropy and single‐ion magnet behaviour with applied external magnetic field is reported. Despite the expected isotropic spin ground state, it has large and positive magnetic anisotropy ( D =+19.2 cm −1 ), which can be attributed to the contribution of quartet excited states (i.e., spin‐admixed character of the ground state).